Ethical Justification of the Value Basis of the European Data Economy Ecosystems - Minna M. Rantanen; Juhani Naskali; Kai K. Kimppa.; Koskinen Jani (Germany, 2022)
Data collection from individuals has become an integral part of society and an asset for global business. This business is realised through data economy ecosystems, which currently are orchestrated from the viewpoint of business. There exist initiatives that aim to change the current situation. One critical component that is missing from data economy ecosystems and development is the values of individuals. To achieve an ethically acceptable data economy, we need to investigate the values of individuals whose data is used. Likewise, those values should be contested, as all values that people may have are not ethically acceptable or possible to implement on a societal level. In this paper, we ethically analyse the individual values that were collected via survey from four European countries. The analysis is based on the three main branches of ethics: Consequentialism, Deontology and Virtue Ethics. It seems that values that individuals have concerning fair data economy are ethically justified and thus should be respected and implemented in policies concerning data economy.
Proceedings of the Conference on Technology Ethics: Turku, Finland, October, 21, 2020